Internet-Based Support for Cardiovascular Disease Management - Sandra Jarvis-Selinger; Joanna Bates; Yuriko Araki; Scott A. Lear (International Journal of Telemedicine and Applications)
With significant declines in cardiovascular disease (CVD) mortality, attention has shifted to patient management. Programs designed to manage CVD require the involvement of health professionals for comanagement and patients' self-management. However, these programs are commonly limited to large urban centers, resulting in limited access for rural patients. The use of telehealth potentially overcomes geographical barriers and can improve access to care for patients. The current research explores how an Internet-based platform might facilitate collaboration among healthcare providers comanaging patients and enhance behavioural change in patients. Forty-eight participants were interviewed including: (a) patients (n=12), (b) physicians (n=11), (c) nurses (n=13), and (d) allied health professionals (n=10). The results were organized and analyzed in three central themes: (1) role of technology for CVD management, (2) challenges to technology adoption, and (3) incentives for technology adoption. Health care providers and patients supported future implementation of Internet-based technology support for CVD management.